W sieci szkolnych gatunków (auto)prezentacyjnych. W poszukiwaniu prototypu - Grzegórzek, Mirosław (Dydaktyka Polonistyczna, 2017)
The article is an attempt to outline the cognitively understood web of school genres used forself-presentation. The author is trying to answer the question of which genre takes the place of theprototype model centre and what relations occur between the genres within the web. The startingpoint for the literary genetics traversing in the linguistic-didactic perspective was the theory of self--presentation as well as both school and extracurricular texts that pursue specified genre patterns. Theprototype is a pattern, the exemplary model of something. On the basis of the comparative studieson school genres used for self-presentation and with the help of metaphorical categories of self-presentation gene and the genotype the self-presentation genre it has been concluded that the prototypeof the self-presentational genre at school is self-characteristics